The vegetation cover anthropization index as a measure of anthropization of natural protected areas. Case: Pico Azul-La Escalera, Mexico - Ramón Puebla, Adonis Maikel (2023)
[Introduction]: Anthropization studies of protected natural areas are generally carried out using fauna studies, grids, and other indicators. [Objective]: To determine the degree of anthropization of a protected natural area using the vegetation cover anthropization index, which takes the physical-geographic landscape as the evaluation unit. [Methodology]: Anthropization was calculated using the vegetation cover anthropization index, which quantitatively and qualitatively evaluates the anthropic modification of the landscapes of a territory, taking as a case the natural protected area Pico Azul-La Escalera, with the support of physical-geographic landscapes, which allows establishing their differentiation in the territory. [Results]: Highly anthropized landscapes represent 2.45% of the territory, are the flattest, and show a predominance of anthropization by agricultural activities; landscapes categorized as anthropized occupy 22.36% of the territory, are related to low-sloping reliefs and optimal soils for agriculture; landscapes with a medium-level index rating cover 24.46% of the area and serve as a buffer zone between the most and least anthropized landscapes; landscapes showing low anthropization values represent 42.13% of the area, and unmodified landscapes represent 8.60% of the area and are the least accessible landscapes with steeper slopes and less fertile soils. [Conclusions]: This proposal is a reliable option for differentiating the degree of anthropization of landscapes and, in particular, for assessing the modification of vegetation cover in a protected natural area.